Efficacy of pirfenidone in patients with idiopathic pulmonary fibrosis with more preserved lung function. Issue 3 (28th July 2016) - Albera, Carlo; Costabel, Ulrich; Fagan, Elizabeth A.; Glassberg, Marilyn K.; Gorina, Eduard; Lancaster, Lisa; Lederer, David J.; Nathan, Steven D.; Spirig, Dominique; Swigris, Jeff J.
This post hoc analysis examined the differences in idiopathic pulmonary fibrosis disease progression and the effects of pirfenidone in patients stratified by more preserved versus less preserved baseline lung function status using forced vital capacity (FVC) or GAP (gender, age and physiology) index stage. Efficacy outcomes, i.e. FVC, 6-min walking distance (6MWD) and dyspnoea (University of California San Diego Shortness of Breath Questionnaire (UCSD SOBQ)), were analysed at 12 months in patients randomised to pirfenidone 2403 mg·day −1 or placebo in the pooled phase 3 CAPACITY/ASCEND population (n=1247), with subgroups stratified by baseline FVC ≥80% versus <80% or GAP stage I versus II–III. Treatment-by-subgroup interaction was tested based on a rank ANCOVA model; factors in the model included study, region, treatment, subgroup and treatment-by-subgroup interaction term. Patients with both more preserved (FVC ≥80% or GAP stage I) and less preserved (FVC <80% or GAP stage II–III) lung function at baseline demonstrated clinically significant disease progression at 12 months in terms of categorical decline in FVC, 6MWD and UCSD SOBQ. The magnitude of pirfenidone treatment effect was comparable between subgroups, regardless of whether lung function was classified using FVC or GAP index stage. These findings support the initiation of treatment with pirfenidone, irrespective of stage of baseline lung function in this patient population. Pirfenidone is efficacious in patients with idiopathic pulmonary fibrosis (IPF) with more preserved lung function http://ow.ly/Ajlt300SR89